2001
DOI: 10.1038/sj.onc.1204783
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin: coupling membrane dynamics to cortical actin assembly

Abstract: Exposure of cells to a variety of external signals causes rapid changes in plasma membrane morphology. Plasma membrane dynamics, including membrane ru e and microspike formation, fusion or ®ssion of intracellular vesicles, and the spatial organization of transmembrane proteins, is directly controlled by the dynamic reorganization of the underlying actin cytoskeleton. Two members of the Rho family of small GTPases, Cdc42 and Rac, have been well established as mediators of extracellular signaling events that imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
396
1
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(411 citation statements)
references
References 217 publications
9
396
1
5
Order By: Relevance
“…In contrast, two extracellular signal-regulated kinase (ERK) sites located at Ser-405 and Ser-418 sites, and ERK phosphorylation enhances cortactin binding and activation of N-WASP (Huang et al, 1998;Campbell et al, 1999;Weed and Parsons, 2001;Martinez-Quiles et al, 2004). Recent studies using mass spectrometry have identified 17 new sites of phosphorylation (12 serine, 4 threonine and 1 tyrosine), suggesting that cortactin is heavily phosphorylated in vivo (Martin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, two extracellular signal-regulated kinase (ERK) sites located at Ser-405 and Ser-418 sites, and ERK phosphorylation enhances cortactin binding and activation of N-WASP (Huang et al, 1998;Campbell et al, 1999;Weed and Parsons, 2001;Martinez-Quiles et al, 2004). Recent studies using mass spectrometry have identified 17 new sites of phosphorylation (12 serine, 4 threonine and 1 tyrosine), suggesting that cortactin is heavily phosphorylated in vivo (Martin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Cortactin, a regulator of ARP2/3-mediated actin polymerization, is known to contribute to tumour cell growth and cancer progression (Weed and Parsons, 2001). Downregulation of cortactin in cancer cell lines decreases the cellular motility and ability to migrate (Rothschild et al, 2006;van Rossum et al, 2006) whereas overexpression resulted in an increased invasive potential (van Rossum et al, 2003;Rothschild et al, 2006).…”
Section: Discussion Cortactin Predicts Poor Survival In Late Stage Lamentioning
confidence: 99%
“…The p130Cas-CRK complex is reported to trigger actin polymerization by a Rac-independent mechanism [29]. Cortactin is an actin-associated scaffolding protein that binds and activates the actin-related protein (Arp) 2/3 complex, structures [39,40]. Cortactin and CRK cooperate to trigger actin polymerization during Shigella invasion of epithelial cells [41].…”
Section: Effect Of Decreasing Crkii Expression On Crkii-p130cas Signamentioning
confidence: 99%